2010
DOI: 10.1039/b915080c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of alkali and alkaline-earth substituted LAMOX oxide-ion conductors

Abstract: The high temperature demixing/recombination phenomenon previously observed in Ca-substituted La(2)Mo(2)O(9) oxide ion conductors [A. Selmi et al., Solid State Ionics, 2006, 177, 3051; Eur. J. Inorg. Chem., 2008, 1813] has been visualised using scanning electron microscopy and EDX analysis. The demixed state appears as CaMoO(4) straight solid streams erupted from pores within LAMOX grains. The thermal stability study is extended to other alkali and alkaline-earth substituted LAMOX compounds, all of which are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…3.58 (8) 3.67 (6) 3.78 73.93 73.78 73.90 74.06 74.11 74.47 (9) 4.65(9) 0.3137 (7) 0.3150 (7) 0.3171 70.3179 70.3188 (6) 0.3193 (6) 0.3171 (7) 0.3169 (8) 0.3185(8) could have changed the overall oxygen vacancy (intrinsic+extrinsic) distribution over the three crystallographic oxygen sites of the structure. Therefore, a second structural model (model 2) was tested, in which a slight 5% depletion of the O1 site to the benefit of O2 or O3 sites was introduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.58 (8) 3.67 (6) 3.78 73.93 73.78 73.90 74.06 74.11 74.47 (9) 4.65(9) 0.3137 (7) 0.3150 (7) 0.3171 70.3179 70.3188 (6) 0.3193 (6) 0.3171 (7) 0.3169 (8) 0.3185(8) could have changed the overall oxygen vacancy (intrinsic+extrinsic) distribution over the three crystallographic oxygen sites of the structure. Therefore, a second structural model (model 2) was tested, in which a slight 5% depletion of the O1 site to the benefit of O2 or O3 sites was introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Whatever the substitute considered, the conductivity decreases nonlinearly as the substitution rate increases. Our previous investigations 7 showed that the β-form of the highest K + -and Ba 2+ -substituted LAMOX exhibit an exsolution of β-KLaMo 2 O 8 and BaMoO 4 scheelite-type phases above a temperature decreasing as the substitute content increases: La 1 is the only composition combining both the "highest" mean La-site cation radius (⟨r⟩ = 1.289 Å) and a stability of the β-form in a temperature range (up to 900°C) as large as the range explored in our previous structural analysis performed on β-La 1.7 Bi 0.3 Mo 2 O 9 derivative, thus allowing a direct comparison. The objective of the current structural analysis on β-La 1.85 Ba 0.…”
mentioning
confidence: 96%
“…Unfortunately, La 2 Mo 2 O 9 presents main drawbacks of poor ionic conductivity at low temperature and degradation in reducing environments. In the last decade, researchers have examined various types of cationic substitutions on La or Mo sites to improve the performance of LAMOX electrolytes [6][7][8][9][10][11][12][13][14]. Several types of substitutions can stabilize the highly conductive β-phase at room temperature, but only substitution of W on the Mo site can effectively improve the phase stability of the electrolyte at low oxygen partial pressures [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…La 2 Mo 2 O 9 undergoes a reversible phase transition at 580 °C from a monoclinic α phase at room temperature to a cubic β phase at high temperature, which causes a 0.53 % abrupt cell volume increase. However, the high temperature cubic β form of La 2 Mo 2 O 9 , which has a higher oxide ion conductivity (6×10 −2 S cm −1 at 800 °C), can be stabilised by various substitutions either on the La site, the Mo site or both . The resulting lanthanum molybdate (LAMOX) family of materials derived through these chemical substitutions of the parent compound La 2 Mo 2 O 9 were considered, at their discovery, as potential electrolyte materials for SOFC devices because of their higher ionic conductivity at intermediate temperature than that of conventional electrolyte yttrium‐stabilised zirconia (YSZ) .…”
Section: Introductionmentioning
confidence: 99%